Butyric Acid Increases the Therapeutic Effect of EHLJ7 on Ulcerative Colitis by Inhibiting JAK2/STAT3/SOCS1 Signaling Pathway - Xiaonan Tang; Xiang Li; Yufei Wang; ZhiHui Zhang; AnJun Deng; WenJie Wang; Haijing Zhang; Hailin Qin; LianQiu Wu (Frontiers Media S.A., 2020)
Ulcerative colitis (UC) is a refractory chronic disease characterized by bloody diarrhea and mucosal or submucosal ulcers. There is an urgent need of new drugs for the treatment of ulcerative colitis. EHLJ7 is a quaternary coptisine derivative. Herein, we explored the therapeutic effect of EHLJ7 on dextran sodium sulfate (DSS)-induced ulcerative colitis (UC) in mice. Results showed that EHLJ7 have good effects on DSS-induced colitis. EHLJ7 significantly improved symptoms induced by DSS including of weight loss, colon contracture, disease activity index (DAI), inflammatory infiltration, and so on. Furthermore, results showed that EHLJ7 could enhance short-chain fatty acids (SCFAs) production especially butyric acid, suggesting that EHLJ7 could improve the metabolic disorder of intestinal flora to a certain extent. Further study indicated that EHLJ7 could cooperate with butyrate to exert its anti-ulcerative colitis effect by inhibiting the activation of janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3)/suppressor of cytokine signaling 1 (SOCS1) pathway. Therefore, EHLJ7 has a potential to be developed as a candidate for the treatment of colitis.